2022
DOI: 10.3389/fneur.2022.772377
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Turning Mobility and Cognitive Function in Chronic Poststroke

Abstract: Turning difficulties are common in patients with stroke. The detrimental effects of dual tasks on turning indicate a correlation between turning and cognition. Cognitive impairment is prevalent after stroke, and stroke patients with mild cognitive impairment had a poorer turning performance than did stroke patients with intact cognitive abilities. Therefore, we investigated the association between turning mobility and cognitive function in patients with chronic poststroke. Ninety patients with chronic stroke (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Six studies out of 21 investigated solely one subjects' group [ 57 , 59 , 64 , 69 , 70 , 77 ]. Other studies included two [ 58 , 61 , 62 , 66 , 71 , 72 ] or three subjects’ groups [ 60 , 63 , 65 , 67 , 68 , 73 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies out of 21 investigated solely one subjects' group [ 57 , 59 , 64 , 69 , 70 , 77 ]. Other studies included two [ 58 , 61 , 62 , 66 , 71 , 72 ] or three subjects’ groups [ 60 , 63 , 65 , 67 , 68 , 73 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies included two [ 58 , 61 , 62 , 66 , 71 , 72 ] or three subjects’ groups [ 60 , 63 , 65 , 67 , 68 , 73 76 ]. Included groups were PD patients [ 57 68 ], stroke patients [ 69 72 ], people with multiple sclerosis [ 75 ], older adults [ 58 , 60 , 62 , 63 , 65 , 67 , 68 , 71 – 76 ], frail and pre-frail older adult [ 73 ], older adult fallers [ 76 ], middle-aged adults [ 74 , 75 ], and young adults [ 74 , 77 ] (Table 1 ). In total, the studied population amounted to 1193 subjects (664 males, 510 females).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few studies that have indirectly analyzed the association between turning function and cognitive impairment. A recent study found that turning function in patients with chronic stroke was associated with cognitive impairment ( Kuan et al, 2022 ). Mirelman et al (2014) also discovered that individuals with MCI had lower trunk angular velocity during turning.…”
Section: Discussionmentioning
confidence: 99%